2020
DOI: 10.3389/fnhum.2020.00295
|View full text |Cite
|
Sign up to set email alerts
|

Brain-to-Brain Coupling in the Gamma-Band as a Marker of Shared Intentionality

Abstract: Cooperation and competition are two ways of social interaction keys to life in society. Recent EEG-based hyperscanning studies reveal that cooperative and competitive interactions induce an increase in interbrain coupling. However, whether this interbrain coupling effect is just a reflection of inter-subject motor coordination or can also signal the type of social interaction is unknown. Here, we show that behavioral coordination and social interaction type can be distinguished according to the frequency of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 73 publications
(96 reference statements)
7
41
0
1
Order By: Relevance
“…Our investigation into the effects of social concordance on interbrain coherence has provided evidence in support of two primary conclusions: (1) that our results are largely in support of interbrain coupling at the gamma band as a biomarker for social concordance manifest here when subject pairs agreed on scenario issues, and (2) that patterns of IBC appear to be sensitive to informational context and content based on IBC variability between the different scenario issues. This study replicated results from previous studies implicating inter-brain gamma activity with core elements of social cognition that underlie social connectedness (Kinreich et al, 2017;Barraza et al, 2020). In our measures of social concordance, we found greater average IBC in agreeing over disagreeing subject pairs (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our investigation into the effects of social concordance on interbrain coherence has provided evidence in support of two primary conclusions: (1) that our results are largely in support of interbrain coupling at the gamma band as a biomarker for social concordance manifest here when subject pairs agreed on scenario issues, and (2) that patterns of IBC appear to be sensitive to informational context and content based on IBC variability between the different scenario issues. This study replicated results from previous studies implicating inter-brain gamma activity with core elements of social cognition that underlie social connectedness (Kinreich et al, 2017;Barraza et al, 2020). In our measures of social concordance, we found greater average IBC in agreeing over disagreeing subject pairs (Figure 2).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are largely consistent with other reports on the relationship between inter-brain gamma activity and social connectedness. A recent study found that inter-brain synchrony in the gamma band was selectively increased between subjects that were playing cooperatively during a reaction time task but not during the competitive trials (Barraza et al, 2020). They found that transient increases in brainto-brain gamma activity during cooperation appeared just prior to and immediately following presentation of stimulus.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This interbrain phase synchrony index has been developed to measure whether the signals from the two interacting individuals are phase locked across time (Lachaux et al, 1999). In line with previous hyperscanning research ( Barraza et al, 2020), the band-pass ltering is applied to the EEG data of each segment of the parent's electrode (φ) and the adolescent's electrode (ψ) to obtain the EEG data of the frequency band of interest. The Hilbert transform is used to analyze the signals of φ and ψ poles in a speci c frequency band, extract phase and subtract, and get PLV of each epoch.…”
Section: Dual-eeg Recording and Data Analysismentioning
confidence: 99%
“…In neuroscience, research on shared cognition among dyads and small groups is captured by aggregating individual member's EEG-WL spectral analysis data (Waldman et al, 2015) wherein EEG-WL is a marker of the cognitive processing required to gather information and compare it to internal mental models. More recent work on neurophysiologic synchronies have now begun to capture the overlap in neural activity among multiple members in a team to capture how much overlap or difference there is in how members pay attention to, react, and process common information (Barraza et al, 2020;Dodel et al, 2020;.…”
Section: Shared Team Cognitionmentioning
confidence: 99%